Influence of Workload, Job Stress And Compensation on Employee Performance At Kopi Kampoeng Id - Wahyu Indah Lestari; Dadang Krisdianto; Khoiriyah Trianti (Universitas Islam Malang, 2024)
This study aims to determine the effect of workload, work stress and compensation on the performance of Kampoeng Id Coffee employees. This type of research is quantitative. The population in this study were Kopi Kampoeng Id employees. The sampling technique used saturated sampling technique with a sample of 30 respondents which were processed using SPSS Statistics 25 software. The data collection technique uses a questionnaire that has been tested for validity and reliability. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that the three research variables have a partial effect, namely with the provisions of the influence of significance that has been tested with SPSS which shows each number in the following variables : t count > t table, namely 2.853 > 1,706 and significant level 0,028 > 0,05 variable workload partially significant effect on employee performance. t count > t table, namely 2,168 > 1,706 and significant level 0,025 > 0,05 the variable of work stress has a significant effect on employee performance. t count > t table, namely 3,355 > 1,706 and significant level 0,019 > 0,05 compensation variables have a significant effect on employee performance. Then simultaneous testing which can be seen from the F value of the variable Workload, work stress, and compensation has a significant effect on employee performance. These results is indicated by the F test obtained Fcount >Ftable, namely 5,551 > 2,98 and Sig. F 0,018 < 0,05. Test the coefficient of determination (Adjusted R Square) that the dependent variable Karuawan's performance (Y) can be explained 45.9% by the independent variables Workload (X1), Work Stress (X2), and Compensation (X3). While the remaining 54.1% is influenced by other variables not examined in this study. The multiple linear analysis test shows that the variable that has the dominant influence on workload is indicated by the greatest beta coefficient value, namely 0.534.